Local Agenda 21: alternative to extend citizen participation and articulation - Oliveira, Celso Maran de; Sousa, Isabel Cristina Nunes de [UNESP] (Univ Caxias Sul, Centro Ciencias Comunicacao, 2023)
The Local Agenda 21 (A21L) is an action plan to ensure better environmental quality for present and future generations that must be participatory. This article aims to discuss and introduce proposals for an increasingly participative process of building the A21L. Through a qualitative approach, the methodology consisted of a literature review, in which we analyzed references to deepen our understanding of the subject. We also search for national statistics on the subject and identify local and international experiences. The results point to an orderly sequence of steps, from planning to the implementation of Local Agenda 21, based on the joint action of all sectors of society. It is an alternative to reach A21L that expands citizen participation and articulation.
Keywords: Local Agenda 21; Democracy; Participation; Sustainability